PENGARUH PENERAPAN MODEL PEMBELAJARAN ROPES PADA MATA DIKLAT GAMBAR TEKNIK TERHADAP HASIL BELAJAR SISWA KELAS X JURUSAN TEKNIK GAMBAR BANGUNAN SMK NEGERI 1 KOTO XI TARUSAN - 686-694 , Angga Permadi (CIVED, 2015)
Abstract This research was motivated by poor learning outcomes in Engineering Drawing subject. In this study, ROPES learning model was applied. The purpose of this study was to determine whether there are anyeffects of the application of ROPES learning model on student learning outcomes fortheoretical part of Engineering Drawing subject of students Class X Building Drawing Engineering Program (TGB) of SMK Negeri 1 Koto XI Tarusan. This research is aquasi-experimental research, using Randomized Control Group Pretest-Posttest Design asthe research design. The population was 28 students of Class X TGB. Two classes of Class X TGB were taken as the sample of the study, with Class X TGB A as the experimental class and Class X TGB B as the control class. The instruments used in this study were a pretest and a posttest in the form of objective questionsamounted to 25 items that have been tested its validity, reliability, difficulty index and discrimination index. Data were analyzed by using t-test (differences of two averages) of Gain Score value (the difference between the pretest and posttest). The results showed that the experimental class had an average score of pretest 43.71 and posttest 81.71, while the control class had an average score of pretest 43.14 and posttest 75.14. It can be seen that there was an increase in the learning outcomes of students in the experimental class. The result of t-test showed that the value of t count = 1,118 and t table = 1,706 at 0.05 level of significance. It can be concluded that the application of ROPES learning model has no significant effect on student learning outcomes fortheoretical part of Engineering Drawing subject. Keywords: ROPES, Hasil Belajar, Gambar Teknik